Morphological and molecular characterization of parabasilids isolated from ex situ nonhuman primates and their keepers at different institutions in Brazil - Dib, Lais Verdan; Barbosa, Alynne da Silva; Correa, Lais Lisboa; Torres, Breno da Silva; Pissinatti, Alcides; Moreira, Silvia Bahadian; Teixeira, Rodrigo Hidalgo Friciello [UNESP]; Costa, André Luíz Mota da; Muniz, José Augusto Pereira Carneiro; Junglos, Amauri Michel; Hirano, Zelinda Maria Braga; Amendoeira, Maria Regina Reis (Elsevier, 2024)
Intestinal protozoa, which can be asymptomatic or cause diarrhea, dysentery and even death, are among the main agents that affect nonhuman primates (NHPs) kept under human care. Nevertheless, information on the molecular and morphometric profiles of parabasilids in the Neotropics is still scarce. In this context, the objective of this study was to isolate the Parabasalia protozoa detected in the feces of NHPs and their keepers in Pavlova and TYSGM9 media and to characterize the isolates by molecular biology and morphometry. Fecal samples from NHPs from five Brazilian institutions were analyzed. Direct examination was performed immediately after obtaining the samples. A total of 511 fecal samples from NHPs were collected, and 10.6% contained parabasilids. Regarding the handlers, of the 74 samples analyzed, three were positive. In vitro-generated parabasilid isolates were successfully obtained from all positive samples, as identified via microscopy. Isolates of the parasite were obtained both from New World NHPs, including the genera Leontopithecus, Saguinus, Leontocebus, Aotus, Saimiri, Sapajus, and Alouatta, and from the Old World primate Pan troglodytes. Forty-nine NHP isolates were molecularly identified: Pentatrichomonas hominis (16), Trichomitus batrachorum (14), Tetratrichomonas brumpti (13) and Hypotrichomonas hampli (6). The human isolates were identified as Tetratrichomonas sp. (2) and T. batrachorum (1). Visualization and morphometric analysis revealed trophozoites with piriform or rounded shapes that presented variable measurements. The isolates previously characterized as P. hominis had up to five free flagella, while T. batrachorum and Tetratrichomonas sp. had up to four free flagella, and H. hampli had a maximum of three free flagella. These morphometric characteristics corroborated the molecular identification. In general, a variety of parabasilids were observed to infect NHPs, and T. batrachorum was isolated from biological samples from both NHPs and their keepers, a finding that reinforces the susceptibility of these hosts to infections by parabasilids in Brazil.
Keywords: Morphological analysis; Neotropical primates; Parabasalia; Phylogeny; Zoonosis